Nutritional Status with Infant Motor Development - Nurwinda Saputri; Eriska Prahasti (IJECA (International Journal of Education and Curriculum Application), 2018)
Children under the age of five (toddler) Indonesia experience nerve development and brain disorders ranging from mild to severe. Every 2 out of 1,000 babies experience motor development disorders. Factors affecting motor development in toddlers, such as hereditary, prenatal environment, postnatal environment. Nutritional status plays an important role in motor development. The purpose of this research is to know the relationship of nutritional status with the development of coarse motor toddler This research is an analytical survey research with cross sectional approach. Sampling techniques used are total sampling. Sample as much as 60 toddlers. This data is collected using checklist and observation sheets. Hypothesis test using Chi square correlation analysis. Data analysis results show the value of P value (0.000) < α (0.05) which means there is a significant relationship as well as the relation of relationships belonging to the strong category with the frequency value of the coefficient of (0.625). In conclusion there is a relationship of nutritional status with the infant motor development, and the relationship of these two variables is significant.